Resistance signatures to oncolytic vesiculoviruses in pancreatic ductal adenocarcinoma - Chelsae R. Watters; Oumar Barro; Musa Gabere; Mia Y. Masuda; Natalie M. Elliott; Elizabeth A. Raupach; Khandoker Usran Ferdous; Mulu Z. Tesfay; Omeed Moaven; Yumei Zhou; Michael T. Barrett; Kenneth H. Buetow; et al. (Molecular Therapy: Oncology)
Pancreatic ductal adenocarcinoma (PDAC) shows limited response to conventional therapies and immunotherapy due to dense stromal barriers and poor immunogenicity. Oncolytic vesiculoviruses hold therapeutic potential for PDAC by lysis of PDAC cells to release tumor-associated antigens, increasing tumor immunogenicity. We previously reported the efficacy of a chimeric vesicular stomatitis virus (VSV) expressing Morreton virus (MorV) glycoprotein in sarcoma. Here, we evaluated the oncolytic potency of MorV and chimeric virus, VMG, in PDAC models. VMG exhibited heterogeneous oncolysis across human PDAC cell lines and PDX cells, similar to parental viruses VSV and MorV. To evaluate potential signatures correlated with resistance to oncolytic vesiculoviruses, we compared transcriptomes of cell lines characterized as sensitive or resistant to oncolysis in vitro. We identified epithelial development and biological adhesion gene sets were significantly associated with vesiculovirus resistance. Additionally, escaped PDAC cells surviving two cycles of infection with VSV showed significant upregulation of stress keratins and downregulation of genes involved in retinoic acid metabolism and cell cycle. An overlapping 39 genes were higher in resistant cell lines at baseline as well as upregulated in escaped PDAC cells. Several resistance-associated genes are targets of anti-cancer therapies in development, offering potential combination approaches with oncolytic vesiculoviruses.